Genetic characteristics, antimicrobial resistance, and prevalence of Arcobacter spp. isolated from various sources in Shenzhen, China - Ma, Yanping; Ju, Changyan; Zhou, Guilan; Yu, Muhua; Chen, Hui; He, Jiaoming; Zhang, Maojun; Duan, Yongxiang (Frontiers in Microbiology, 2022)
Worldwide, Arcobacter spp. is an emerging zoonotic and foodborne pathogen. However, we know little about its prevalence and antimicrobial resistance in China. To investigate the prevalence of Arcobacter spp. from different sources, 396 samples were collected from human feces; chicken cecum; and food specimens, including chicken meat, beef, pork, lettuce, and seafood. Arcobacter spp. was isolated using the membrane filtration method. The agar dilution method and next generation sequencing for 92 strains were used to investigate antimicrobial resistance and to obtain the whole-genome data respectively. The virulence factors database (VFDB) was queried to identify virulence genes. The ResFinder and Comprehensive Antibiotic Resistance Database (CARD) were used to predict resistance genes. Phylogenetic tree was constructed using the maximum likelihood (ML) method with core single nucleotide polymorphisms. We found that 27.5% of samples (n = 109) were positive for Arcobacter spp., comprising A. butzleri (53.0%), A. cryaerophilus (39.6%), and A. skirrowii (7.4%). The highest prevalence was observed in chicken meat (81.2%), followed by seafood (51.9%), pork (43.3%), beef (36.7%), lettuce (35.5%), chicken cecum (8%), and human feces samples (0%, 0/159). Antimicrobial susceptibility tests revealed that 51 A. butzleri and 40 A. cryaerophilus strains were resistant to streptomycin (98.1%, 70%), clindamycin (94.1%, 90%), tetracycline (64.7%, 52.5%) azithromycin (43.1%, 15%), nalidixic acid (33.4%, 35%), and ciprofloxacin (31.3%, 35%), but were susceptible to erythromycin, gentamicin, chloramphenicol, telithromycin, and clindamycin (≤10%). The virulence factors tlyA, mviN, cj1349, ciaB, and pldA, were carried by all Arcobacter spp. strains, followed by cadF (95.7%), iroE (23.9%), hecB (2.2%), hecA and irgA (1.1%). Only one A. butzleri strain (F061-2G) carried a macrolide resistance gene (ereA). One A. butzleri and one A. cryaerophilus harbored resistance island gene clusters, which were isolated from pork and chicken, respectively. Phylogenetic tree analysis revealed that A. butzleri, A. cryaerophilus and A. skirrowii were obviously separated. To the best of my knowledge, this is the first report of the isolation of Arcobacter spp. from vegetables and seafood in China. The resistance island gene cluster found in pork and chicken meat and presence of virulence factors could be a potential risk to human health.